Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0068821
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale for Consuming Cognitive Enhancement Drugs in University Students and Teachers

Abstract: Cognitive enhancement (CE) is the pharmaceutical augmentation of mental abilities (e.g., learning or memory) without medical necessity. This topic has recently attracted widespread attention in scientific and social circles. However, knowledge regarding the mechanisms that underlie the decision to use CE medication is limited. To analyze these decisions, we used data from two online surveys of randomly sampled university teachers (N = 1,406) and students (N = 3,486). Each respondent evaluated one randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 82 publications
(129 reference statements)
11
54
1
Order By: Relevance
“…In particular, helping students to manage stress at a considerable level may be helpful by identifying less-harmful methods (26). The results of Sattler et al study showed that students tended to enhance their cognitive performance by drugs compared to university teachers; however, the overall willingness was low (27). The desired goal of CE medication use is to increase the cognitive performance by increasing concentration, increasing the time of the study, or increasing the working memory performance (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, helping students to manage stress at a considerable level may be helpful by identifying less-harmful methods (26). The results of Sattler et al study showed that students tended to enhance their cognitive performance by drugs compared to university teachers; however, the overall willingness was low (27). The desired goal of CE medication use is to increase the cognitive performance by increasing concentration, increasing the time of the study, or increasing the working memory performance (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…[28,33], see the discussion section for limitations of this approach). We experimentally varied five characteristics (dimensions) of this drug (magnitude, probability of enhancement effect, severity, probability of side effects, and drug price), and three characteristics of the social environment (peer prevalence, social disapproval, and social suggestions; see Table  2).…”
Section: Methodsmentioning
confidence: 99%
“…However, work in ADHD populations, including several randomised control trials, indicates that the psychostimulants are associated with relatively mild side effects such as a dry mouth [20,21]and reduced appetite but also more serious effects of increased in heart rate and blood pressure [21][22][23][24]. Comparative studies have found, perhaps unsurprisingly, that users are less concerned about the safety of smart drugs than non-users [6,25], and perceptions of the severity of possible health risks have been inversely associated with willingness to use smart drugs [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%